Linking energy scenarios and waste storylines for prospective environmental assessment of waste management systems. (November 2018) - Meylan, Grégoire; Haupt, Melanie; Duygan, Mert; Hellweg, Stefanie; Stauffacher, Michael
Graphical abstract: Highlights: A novel approach is presented to construct energy and waste scenarios. Joint scenarios are used in prospective life cycle assessment of waste management. The approach relies on existing energy scenarios and waste storylines. Waste storylines are developed in close interaction with stakeholders. The approach is applied to the case of Swiss municipal solid waste management. Abstract: Multiple international and supranational organizations call upon changes in current waste management practices to play a key role in developing more sustainable economies. Life cycle assessment (LCA) is a popular method used to assess the sustainability of future waste management options. The uncertainties about future energy systems and waste compositions, however, may lead to ambiguous LCA results. One way to deal with this challenge is the development of joint energy and waste scenarios to investigate the robustness of waste management options. To date, joint energy and waste scenarios rely on the integration of large economic and engineering models. Complex models can hamper the transparency required for decision-makers to understand and implement LCA recommendations. Here we present the alternative of combining diverse energy scenarios and stakeholder-based waste storylines. This is a more qualitative approach than previous sustainable energy/waste evaluations and has a double aim: to address upfront the energy and waste composition sensitivity and enhance transparency by both relying on well-documented energy scenarios and involving stakeholders in the waste storyline formulation. We apply the approach to the Swiss municipal solid waste (MSW) management system in the context of the energy transition away from nuclear power. Three energy scenarios capture how radical the transition might be, while the storylines reflect societal developments and waste policies leading to low, high, and average MSW amounts. The approach delivers feasibility spaces of energy systems and waste compositions as input to the LCAs. It ensures a high level of transparency, which, in conjunction with the participation of decision-makers, has the potential to increase the chances of implementation of the recommendations based on LCA results.